EKSISTENSI DAKWAH AJARAN TAREKAT KHALWATIYAH SAMMAN DI KABUPATEN WAJO - Nurhikmah, Nurhikmah (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
This research aims to know more closely about the Khalwatiyah as described in the main problem of research object, namely the existence of appeal of Khalwatiah in Wajo Regency. The concept of appeal and the form of the practice of the teachings of the Khalwatiyah Samman in Wajo Regency formed from the strategy of appeal, the Khalifah (teachers) in the Khalwatiyah school, the faithful promise (baiat) which became the member in Khalwatiyah, the remember to God (zikir) done consistently and the figure used as guidance. Supporting factors in the Khalwatiyah because the city of Sengkang where the dominant of Khalifah Puang Lompo who is the old man of the Khalifah in Patte'ne whose existence is supported by the government and all descendants of the Khalifah and its followers. The inhibition of its existence does not move structurally organizational so that Khalwatiyah in Wajo developed naturally from the descendants and some of the sympathizers who eventually became followers in the teachings of the Khalwatiyah of Wajo Regency.